Analysis of Challenges and Prospects for Dispute Resolution through the National Sharia Arbitration Board in the Indonesian Legal Context - Judijanto, Loso; Harsya, Rabith Madah Khulaili; Prananingrum, Dwi Kartika; Saryanto, Saryanto; Retnaningsih, Rahayu (Westscience Press, 2024)
This research explores the challenges and prospects for dispute resolution through the National Sharia Arbitration Board within the Indonesian legal context. Utilizing qualitative research methods, including interviews, case studies, content analysis, and comparative analysis, the study identifies institutional challenges such as resource constraints, procedural complexities, and limited jurisdiction. Legal and cultural factors, including the harmonization of laws, cultural sensitivity, and gender equity, are examined. Case studies illustrate the Board's efficacy in family disputes while revealing challenges in handling commercial disputes. Prospects for future development encompass legal reforms, capacity building, and public awareness initiatives. A comparative analysis with global Sharia arbitration bodies provides insights into shared challenges and distinctions. The implications for the Indonesian legal system highlight the need for strategic interventions. Overall, this research contributes to a nuanced understanding of the National Sharia Arbitration Board's role and suggests pathways for its sustainable development